Is tennis a predisposing factor for degenerative shoulder disease? A controlled study in former elite players - Maquirriain, J.; Ghisi, J. P.; Amato, S. (British Journal of Sports Medicine, 2006)
Background: High demands imposed to the shoulder during tennis activity can decrease the efficiency of static and dynamic constraints. Subtle or frank instability of the glenohumeral joint may occur, and long term degenerative changes may be expected.